A new visual rating scale for Ioflupane imaging in Lewy body disease - Jim J. Lloyd; George Petrides; Paul C. Donaghy; Sean J. Colloby; Johannes Attems; John T. O'Brien; Gemma Roberts; Alan J. Thomas (NeuroImage: Clinical, 2018)
Background: Dopaminergic loss on 123I-Ioflupane brain imaging is a recognised biomarker for dementia with Lewy bodies. It is usually assessed using a visual rating scale developed for Parkinson's disease, which may not be optimal for dementia with Lewy bodies, as patterns of dopaminergic loss can be different. Objectives: We aimed to develop a new visual rating scale for 123I-Ioflupane brain images in Lewy body disease that encompasses appearances seen in dementia with Lewy bodies, and validate this against autopsy diagnosis. Methods: Four experienced observers developed and tested a new scale consisting of two metrics, reflecting overall loss and heterogeneity of loss. 66 subjects were used during development including clinical diagnoses of Alzheimer's disease (n = 14), Parkinson's disease (n = 9), Parkinson's disease dementia (n = 9), dementia with Lewy bodies (n = 15) and normal controls (n = 19). The scale was then tested on an independent group of 46 subjects with autopsy confirmed diagnosis: Alzheimer's disease (n = 11), Parkinson's disease (n = 3), Parkinson's disease dementia (n = 15), dementia with Lewy bodies (n = 12), normal controls (n = 4) and Frontotemporal dementia (n = 1). Results: In the autopsy validation the sensitivity and specificity of the new scale for Lewy body disease was 97% and 100% respectively, compared with the standard scale which had the same sensitivity (97%), but lower specificity (80%). The new scale had excellent inter rater reliability (intra-class correlation coefficient 0.93). Conclusion: A new robust and reliable rating scale is described that straightforwardly captures the visual appearance of 123I-Ioflupane brain images. It demonstrated high accuracy in autopsy confirmed cases and offers advantages over the existing visual rating scale. Keywords: Visual rating, Loflupane, FP-CIT, Dementia with Lewy bodies, Dopaminergic imaging, Lewy body disease